Paciente de 58 años de edad de sexo masculino con fibrosis pulmonar más neumonía. - Manchay Mendoza, Johanna Ibeth (2020)
The clinical case is about a 58-year-old patient who has a fever greater than 38 ° C, cough, dyspnea, sore throat; they are prescribed antiviral as initial treatment but a few hours later he enters a severe bronchospasm crisis, a round of salbutamol was performed every 15 minutes, he is nebulized with ipatropium bromide and dexamethasone, he is placed intravenously prednisolone, magnesium sulfate and aminophylline but the patient does not come out of crisis and proceeds to intubate and connect to mechanical ventilation. After performing the corresponding examinations, a diagnosis of pulmonary fibrosis + COPD with lower respiratory tract infection was reached. The present clinical case seeks to justify the importance of knowing how patients with pulmonary fibrosis can lead a quiet life and monitor the progress of the disease since although it is true there is no cure for this condition but it is treatable and a person suffering from it You can relieve your symptoms with care and rehabilitation in the same way avoiding possible complications. The main objective is to show how to help a patient with pulmonary fibrosis to obtain a good quality of life by coping with his illness. It was concluded that these patients are going to be exposed to infections, especially respiratory infections, so it is very important that the patient lives in an environment suitable to their health condition and as we know the living environment has a great influence on the proliferation and evolution of these infections.